Impact assessment of National Mushroom Mela - Shirur, Mahantesh; Vijay, B; Manikandan, K; Wakchaure, G C; Taank, Vikas; Verma, Sunil; Bhatia, Reeta (Mushroom Research, 2011)
Despite various ICT tools for information dissemination, melas continue to be a significant mode of transfer of technology owing to many advantages. Face-to-face interaction, live demonstration of technologies, learning from other growers, etc are important components of mela. The present study was conducted to assess the impact of annual National Mushroom Mela organized by Directorate of Mushroom Research, Solan on 10 Â September every year. The increasing impact of national mushroom mela with respect to participation of stakeholders in the mela over recent years was witnessed. Due to proximity and high mushroom growing activity, participation from North India is significant. The meager participation of people from North Eastern India was conspicuously observed. Over a period of one decade, the National mushroom mela has extended its impact from provincial to Pan India as seen by the participation from most states of the country in the last three years. The farmersâ€™ problems with respect to marketing, processing and disease incidence seek intervention of the scientists to address these issues on priority. Looking at the scope of the melas in India, they hold much more relevance for mushroom growers considering the novelty of the crop and the special knowledge it demands for its cultivation.